2014
DOI: 10.1002/14651858.cd007411.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for male subfertility

Abstract: There is low quality evidence from only four small randomised controlled trials suggesting that antioxidant supplementation in subfertile males may improve live birth rates for couples attending fertility clinics. Low quality evidence suggests that clinical pregnancy rates may increase. There is no evidence of increased risk of miscarriage but this is uncertain as the evidence is of very low quality. Data were lacking on other adverse effects. Further large well-designed randomised placebo-controlled trials ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
216
1
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 227 publications
(232 citation statements)
references
References 95 publications
4
216
1
11
Order By: Relevance
“…Cochrane databases showed both clinical pregnancy and live birth rate increased significantly after using antioxidants in subfertile men. Though dose schedule were varied in different studies net outcome is comparable with our study [61,62].…”
Section: Discussionsupporting
confidence: 81%
“…Cochrane databases showed both clinical pregnancy and live birth rate increased significantly after using antioxidants in subfertile men. Though dose schedule were varied in different studies net outcome is comparable with our study [61,62].…”
Section: Discussionsupporting
confidence: 81%
“…Попытки метаанализа данных о значении измерения ФДС в репродукции показывают, что од-нозначного ответа дать нельзя, результаты весьма про-тиворечивы: нет данных о предиктивности теста, не подтверждаются данные о преимуществе ИКСИ перед ЭКО при повышенной фрагментации ДНК [84,[93][94][95][96]. Авторы отмечают низкое качество рандомизированных исследований и считают, что рекомендовать тест для универсального использования рано: есть работы, в ко-торых не найдено различий исхода ВРТ и беременно-сти при различиях в содержании ФДС, исследованы небольшие гетерогенные популяции, исследования про-водятся разными методами и различаются по дизайну экспериментов.…”
Section: корреляционная электронная микроскопияunclassified
“…Большое количество клинических исследований посвящено изучению влияния антиоксидантной терапии при по-вышенном содержании сперматозоидов с ФДС (см. об-зоры [96,117]). Антиоксидантная терапия действительно снижает содержание сперматозоидов с ФДС, но дан-ные о достижении клинической беременности далеко не всегда совпадают с данными о нормализации пока-зателей фрагментации ДНК в сперматозоидах.…”
Section: корреляционная электронная микроскопияunclassified
“…Improvements in sperm motility, sperm DNA fragmentation, fertilization capacity, and odds of normal sperm count were observed in most studies [120][121][122][123], albeit, in a few of them, no advantage was documented [124,130]. A Cochrane metaanalysis on the use of oral antioxidants in male infertility found that these agents significantly improved pregnancy rates and live births and decreased sperm DNA damage [131]. Nevertheless, improvements in semen parameters are not well evident [131] (Table 7).…”
Section: Prescription Of Antioxidantsmentioning
confidence: 99%
“…A Cochrane metaanalysis on the use of oral antioxidants in male infertility found that these agents significantly improved pregnancy rates and live births and decreased sperm DNA damage [131]. Nevertheless, improvements in semen parameters are not well evident [131] (Table 7). These observations support the concept that antioxidants can improve sperm function by improving sperm DNA integrity and fertilizing capabilities.…”
Section: Prescription Of Antioxidantsmentioning
confidence: 99%